Komfort wewnętrzny i systemy reprezentacji w edukacji wczesnoszkolnej przez sztukę = Internal comfort end representation systems in early school education through the art - Sikora-Leśna, Irena (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
The author draws attention to the positive possibilities of triggering a child with self-esteem, anxiety, or even stress. Looks at different learning styles. It negates the role of memory learning and decomposition. Indicates the effects of adult behavioral patterns.
Keywords: bezpieczeństwo wewnętrzne; muzykoterapia; fonoterapia; arteterapia; wizualizacja; afirmacja; relaksacja; style uczenia się; internal safety; music therapy; phonetic therapy; art therapy; visualisation; suggestions; affirmative activities; relaxation; styles of learning